Penyuluhan Pemanfaatan Campuran Kulit Umbi Ubi Kayu dan Daun Ubi Kayu Fermentasi dalam Ransum Puyuh Petelur di KWT Melati Mini Limau Manis Kota Padang - Kadran Fajrona; Mirnawati Mirnawati; Ade Djulardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Women Farmers Group of Melati Mini is a livestock group engaged in poultry farming, especially for quail commodities. The livestock business managed by the group faces the problem of high feed prices so that the profits obtained by farmers are low. Local feed ingredients, such as cassava tuber skin and leaves, can be used for alternative feed. Regarding availability, those two ingredients are abundant, but their utilization in rations is relatively low due to poor quality. The fermentation process can improve the nutrient quality of those local feed ingredients using the fungus Rhizopus oligosporus. The community service activity was conducted using the counselling method, including introducing the ingredients used for fermentation, how to ferment, and preparing rations for quail farming. Twenty participants of Melati Mini's members attended the activity to gain knowledge previously did not know that those two materials could be used for poultry feed.